INFLUENCE OF QUALITY OF PARENT-CHILD RELATIONSHIP AND PARENTAL COMMUNICATION STYLES AMONG INSCHOOL ADOLESCENTS IN ONDO STATE, NIGERIA - Ogunsanmi, ,; Olusanya, ,; Olusanya, , (European Scientific Journal, ESJ, 2014)
Abstract The growth of STIs, early sexual initiation, unwanted pregnancy and abortion among adolescents in Sub-Saharan Africa, particularly in Nigeria can be attributed to inadequate communication about sexuality within the family. Despite earlier studies at understanding the process of parent-child communication, peers continue to be the major source of information on sexrelated matters for adolescents. This situation has resulted in distorted information about sex-related matters for adolescents which is evident in the prevalence of risky sexual behaviour and its attendant negative grave consequences among adolescents. The study investigated the influence of parent-child relationship quality on communication styles of parents with their adolescents on sex-related matters. The study was a descriptive design of the survey type. It used in-school adolescents in from the three senatorial districts in Ondo State. The sample consisted of 588 in-school adolescents from three Local Government Areas in Ondo state. Questionnaire was the instrument of data collection. Findings revealed that 56.6% of the subjects did not talk about sex with their parents while 66.7% indicated that they did get along with their parents and discussed intimately with them. Also, the quality of parent-child relationship has a significant relationship with parental communication styles. It was recommended that reorientation and integration of parents into various intervention programmes on adolescent’s sexual behaviour are needed in the society.